Isotopic Characteristics of Neogene‐Quaternary Tephra From IODP Site U1438: A Record of Explosive Volcanic Activity in the Kyushu‐Ryukyu Arc. (16th May 2019) - McCarthy, Anders; Yogodzinski, Gene; Tepley, Frank J.; Bizimis, Michael; Arculus, Richard; Ishizuka, Osamu
Abstract: International Ocean Discovery program (IODP) Site U1438 is located within the Amami‐Sankaku Basin, ~50 km SW of the Kyushu‐Palau Ridge and ~500 km SE of the present‐day volcanic front of the Kyushu‐Ryukyu arc. Thirty‐eight rhyolitic tephra layers (1–15 cm thick) deposited over the last 4 Myr were recovered at this site. Representative ash layers dominated by unaltered, colorless glass shards reaching 100–300 μm in size, in association with rare pyroxene, amphibole, biotite, and zircon, were sampled for isotopic analysis. The isotopic compositions of the tephra have a narrow range in 87 Sr/ 86 Sr (0.704 to 0.706), 206 Pb/ 204 Pb (18.32 to 18.46), 207 Pb/ 204 Pb (15.57 to 15.62), and 208 Pb/ 204 Pb (38.46 to 38.75) and are more variable in ε Nd (−3.5 to +4.8) and ε Hf (+2.0 to +13.3). This record indicates the tephra were not sourced from the Izu‐Bonin‐Mariana arc or from Central Japan but derived from felsic volcanism from the Kyushu‐Ryukyu arc. The 4.8‐km‐deep Amami‐Sankaku Basin was located up to 600–900 km from the Kyushu‐Ryukyu arc over the last 4 Ma, which is significantly more distal than other drill sites from which extensive tephra layers sourced from SW Japan have been recovered. Site U1438 tephra are thus likely related to widely distributed ( M > 6) rhyolitic eruptions. We propose the unique tephra record and high‐precision isotope analysis of recovered tephra from Site U1438 can be used as an important marker to identify submerged calderas within the Ryukyu arc and/or constrain the history of activity (>1 Ma) of major calderas‐forming eruptions within the Kyushu‐Ryukyu arc. Key Points: IODP Site U1438 records a unique 4‐Ma history of rhyolite eruptions from the Kyushu‐Ryukyu arc Explosive (>6 M) eruptions at 4 Ma, 2–2.5 Ma and <1 Ma in southwest Japan recorded in deep ocean basin (Amami‐Sankaku Basin) Radiogenic isotopes of tephra might be key to distinguish the source of eruptive products